Abkhazia – 2018: The Dynamics of Domestic Political Process in the Prospect of Presidential Election - Vladimir Novikov (Международная аналитика)
The paper considers the dynamics of the domestic political process in the Republic of Abkhazia in 2018. The pivot of this process was the presidential election campaign that started in 2018. The author makes an attempt to analyze the activities of both the current authorities and the opposition. The events of early 2018 related to the pardon of Georgy Lukava revitalized the slogan of early resignation of President Raul Khajimba that was taken off after the December 2016 agreements. The main dilemma the opposition faces now is that it cannot ignore the street protest but at the same time does not aspire the repetition of 2014 events. Special attention is paid to the positioning of ex-President Alexander Ankvab in relation to the authorities and the opposition. The struggle is also considered within originally pro-authorities forces (evidenced by the rivalry around the position of prime-minister and searching of an alternative to Khajimba as President) which, up to December 2018, led to some signs of split among Khajimba’s supporters. The author makes some short-term forecasts; in particular, he suggests that ex-Chairman of the State Security Council Astamur Tarba (who announced in March 2019 his intention to be nominated to the presidency) could count upon former supporters of Khajimba who had been disappointed in the current Head of State. Analyzed are also attempts to create “a third force” (“Common Cause”) as an alternative to both the authorities and the opposition. In conclusion, the pre-election alignment of forces and possible results of the election are considered, with special attention to the influence of Aslan Bjania’s illness on the electoral process.